1995
DOI: 10.5254/1.3538741
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ultrasonic Technology for Devulcanization of Waste Rubbers

Abstract: A novel patented process and several reactors have been developed for devulcanization of waste rubbers. The technology is based on the use of the high power ultrasonics. The ultrasonic waves of certain levels in the presence of pressure and heat rapidly break up the three-dimensional network in crosslinked rubbers. The devulcanized rubber can be reprocessed, shaped and revulcanized in much the same way as a virgin rubber. The first laboratory reactor has been scaled up to pilot-plant level by the National Feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
118
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 182 publications
(121 citation statements)
references
References 0 publications
1
118
2
Order By: Relevance
“…In general, it can be observed that the optimum cure time and scorch time, represented by t 90 and ts 1 respectively, were lower for samples with the highest exposure times to microwaves in one step as well as in multistep treatments. This behavior is characteristic of reclaimed rubber and it was observed by some other authors [14][15][16][17] , which probably happens due to the presence of residual curatives from the first vulcanization. The devulcanization process increases the freedom degree of the polymeric chains, accelerating the reaction with the increasing of the exposure time of the GTR to microwaves, possibly due to the great amount of effective shocks during the process.…”
Section: Revulcanization Characteristicsmentioning
confidence: 70%
“…In general, it can be observed that the optimum cure time and scorch time, represented by t 90 and ts 1 respectively, were lower for samples with the highest exposure times to microwaves in one step as well as in multistep treatments. This behavior is characteristic of reclaimed rubber and it was observed by some other authors [14][15][16][17] , which probably happens due to the presence of residual curatives from the first vulcanization. The devulcanization process increases the freedom degree of the polymeric chains, accelerating the reaction with the increasing of the exposure time of the GTR to microwaves, possibly due to the great amount of effective shocks during the process.…”
Section: Revulcanization Characteristicsmentioning
confidence: 70%
“…They include thermal process, heater or pan process, and digester process, [8][9][10][11][12][13][14][15] [30][31][32][33][34][35][36][37][38][39] thermomechanical. 40 thermochemical, [41][42][43][44][45][46][47][48] ultrasonic devulcanization, [49][50][51][52][53][54][55] and many other less efficient methods. 56,57 Numerous techniques for recycling rubber waste have also been developed.…”
Section: Discussionmentioning
confidence: 99%
“…They are autoclave, 82 microwaves heater, [83][84][85] , ultrasonic reactor, [49][50][51][52][53][54][55]80 twin screw extruder, 86,87 and internal batch mixer. 6,58,59 The analytical methods for testing and characterizing devulcanized rubber waste are: solvent swelling, 88 thermogravimetry analysis (TGA), 64,74,76,78 solid-State H neutron mass spectroscopy (NMR), 93,95-100 differential scanning calorimeter (DSC), 101 atomic absorption spectroscopy, 93,101 inductively coupled plasma atomic emission spectroscopy (ICP-AES), 93,101 inductively coupled plasma optical emission spectroscopy (ICP-OES), 93,101 and elemental analysis which involves the determination of the mass fraction of carbon, hydrogen, nitrogen, 93,101 and heteroatoms (X) (CNHX).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations